Nurse managers' role in older nurses' intention to stay. Issue 1 (16th March 2015) - Armstrong-Stassen, Marjorie; Freeman, Michelle; Cameron, Sheila; Rajacic, Dale
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose and test a model of the underlying mechanisms linking perceived availability of human resource (HR) practices relevant to older nurses and older nurses' intentions to stay with their hospitals. Design/methodology/approach – Quantitative data were collected from randomly selected older registered nurses (N=660) engaged in direct patient care in hospitals in Canada. Structural equation modelling was used to test the hypothesized model. Findings – The relationship between perceptions of HR practices (performance evaluation, recognition/respect) and intentions to stay was mediated by the perceived fairness with which nurse managers managed these HR practices and nurse manager satisfaction. When nurse managers were perceived to administer the HR practices fairly (high perceived procedural justice), older nurses were more satisfied with their nurse manager and, in turn, more likely to intend to stay. Research limitations/implications – The cross-sectional research design does not allow determination of causality. Practical implications – It is important that nurse managers receive training to increase their awareness of the needs of older nurses and that nurse managers be educated on how to manage HR practices relevant to older nurses in a fair manner. Equally important is that hospital administrators and HR managers recognize the importance of providing such HR practices and supporting nurse managers in managing these practices. Originality/value – The findings increase the understanding of how HR practices tailored to older nurses are related to the intentions of these nurses to remain with their hospital, and especially the crucial role that first-line nurse managers play in this process.